The Impact of Radiotelephony Practice on Developing Communication Skills in Aviation for Initial Student Pilots - Refly R. Woisiri; Agus Setiawan; Rizqi Claudia Wardani. H (TEKILA: Journal of Language Teaching and Literature, 2024)
This study examines the impact of radiotelephony practice on the speaking and listening skills of initial student pilots at the Lombok Institute of Flight Technology, emphasizing its role in developing essential communication competencies. Employing a pre-experimental design with pretest and posttest assessments, the research involved a sample of seven students. Standardized speaking and listening tests were used to collect data, which was analyzed using the paired T-test in SPSS software. The results demonstrated significant improvements in both speaking and listening skills, with T-test scores confirming statistical significance (p < 0.05). Speaking scores improved notably, with four students achieving fair scores and three attaining good scores in the posttest, compared to predominantly poor scores in the pretest. Listening skills also improved by an average of 20 points, although they remained within the poor classification, highlighting a critical area for further intervention. This study’s focus on initial student pilots offers a novel perspective, showcasing the potential of targeted radiotelephony practice in building foundational communication skills necessary for professional aviation roles. The findings underscore the need for continued practice and tailored strategies to address listening skill gaps, ensuring comprehensive communication proficiency for aspiring pilots.